Strategy For Sustainability Of Micro, Small, Medium Enterprises Trowulan Stone Patterns Based On Swot Analysis - Ilham, Rachmad; Churiyah, Madziatul (International Journal of Business, Law, and Education, 2024)
MSMEs provide substantial benefits in terms of income for most communities as well as encouraging creativity in line with maintaining local traditions and culture. The purpose of this study is to identify and propose new strategies that can help stone sculpture artisans in Trowulan improve competitiveness and business sustainability. The research method is descriptive qualitative with data collection through interviews. The results show that a holistic management strategy, ranging from strength-opportunity utilization to weakness-threat mitigation, helps Trowulan stone sculpture MSMEs strengthen their position in the market and achieve sustainable growth. This can be done by marketing and cooperation with the government and among craftsmen to face market changes and external threats.